Cooperative Learning Strategies to Reinforce the EFL Learners' Speaking Skill: A Review of Literature - Bousbai, Abdelaziz; Hamdini, Nariman (جامعة قاصدي مرباح - مخبر تطوير الممارسات النفسية والتربوية, 2019)
يسعى الباحثون الجامعيون والتربويون، بما فيهم الجزائريون، بشكل مستمر إلى اعتماد أفضل أساليب التدريس والتقنيات التي من شأنها أن توفر النتائج المرجوة. في عالم العولمة، وتزايد الحاجة إلى الإنجليزية للعديد من الأغراض في مختلف أماكن العمل، أصبح إتقان اللغة الإنجليزية أمرا ضروريا. لأجل ذلك، أي لتلبية احتياجات المتعلمين، تم اعتماد مجموعة متنوعة من الأساليب والتقنيات والاستراتيجيات لتحقيق معالجة أفضل للغات الأجنبية تقترح الدراسة الحالية طريقة تدريس- التعلم التعاوني - والتي يعتقد أنها مفيدة لكل سواء لمعلمي اللغة الإنجليزية أو للمتعلمين لتحقيق الأهداف والتغلب على بعض عقبات التعلم. لقد ثبت أن التعلم التعاوني فعال في تحسين وتعزيز مهارات التحدث للمتعلمين.
University researchers and educationists, including the Algerians, are continually seeking to adopt the best teaching methods and techniques that would provide the desired results. In a globalized world, and the need for English for many purposes in different workplaces, a good command of English has become a necessity. To meet the learners' needs, a variety of approaches, methods, techniques, and strategies are adopted to achieve a better manipulation of foreign languages. The current study suggests a teaching technique -- cooperative learning -- which is believed to be useful for both English language teachers and learners to achieve the objectives and overcome some learning obstacles. Cooperative learning has been proved to be effective in improving and reinforcing the learners’ speaking skills.
Keywords: التعلم التعاوني -- طرائق التدريس -- اللغة الإنجليزية -- مهارة التحدث